The Tripartite Structure of Religious Freedom in China - WANG Shucheng (Journal of Research for Christianity in China (JRCC), 2025)
It is believed that China has developed a tripartite religious market: the red market comprising government-supported religions, the black market consisting of religions targeted by government crackdowns, and the gray market formed by folk religions and spiritual groups. Furthermore, though rarely acknowledged, China has indeed established a legal framework for managing religious affairs. This paper argues that religious freedom is also tripartite and develops a corresponding tripartite legal theory. This framework helps elucidate the extent to which religious freedom is protected under Chinese law and its status within a non-liberal context. Specifically, it encompasses three tiers: conditional religious freedom, limited religious freedom, and prohibited religious freedom. Furthermore, this constitutes a dynamic, resilient tripartite model compatible with authoritarianism under Communist Party leadership.